"Thank you for reaching out:" Brand relationship management and the conversational human voice of customer care in online service encounters. (April 2022) - Creelman, Valerie
Abstract: Motivated by increased calls for research on language use in service encounters, this study examines how customer care agents working in the retail banking sector linguistically operationalize a conversational human voice in their online service encounters to support brand-customer relationships on social media. Applying a rhetorical move analysis framework to an extensive corpus of customer care agents' responses to customers' queries, comments, and complaints on Facebook, this study describes the discourse structure of these responses to identify the conventionalized moves performing the relational work in these brief online encounters. By examining the linguistic features that characterize these moves, my findings confirm that the linguistic elements supporting message personalization, positive politeness strategies, and invitational rhetoric collectively create the recognizable conversational voice that supports agents' efforts to initiate and manage brand-customer relationships online. My findings also highlight the role of digital punctuation and emoji usage to support positive politeness strategies and to communicate agents' attitudinal stance in their efforts to deliver service with a smile in an online environment. Finally, this study calls attention to and provides insights into language usage, online social interaction, and webcare discourse within one facet of the banking services industry.